2019
DOI: 10.1111/1750-3841.14649
|View full text |Cite
|
Sign up to set email alerts
|

Tartary Buckwheat Extract and Chitosan Coated Tilapia (Oreochromis Niloticus) Fillets Determine Their Shelf Life

Abstract: The preservation effects of tartary buckwheat extract (T) and chitosan (C) coatings on the physicochemical (pH value, thiobarbituric acid value, Peroxide value (PV), total volatile basic nitrogen (TVB‐N), K value, surface color and the texture profiles), bacteriological (total viable counts (TVC) and psychrotrophic bacteria counts (PBC)), and sensory characteristics of tilapia (Oreochromis niloticus) fillets storage at 0 °C for 18 days were evaluated. The fillets coated with 0.5% T + 1.0% C, 1.0% T + 1.0% C an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
2
6
0
Order By: Relevance
“…Moreover, AP + 2.0% CS was more effective than AP + 1.0% CS to inhibit nucleotide degradation for the same storage conditions. The results were similar to Yang et al (2019), which indicated that CS contained tartary buckwheat extract could effectively delay the ATP decomposition and quality deterioration of tilapia fillets. Zhu, Ma, Yang, Xiao, and Xiong (2016) suggested that the sharp increase of K ‐value lead to the decline of freshness and satisfying flavor, which mainly because of IMP rapidly broke down into HxR and Hx in fish meat.…”
Section: Resultssupporting
confidence: 89%
“…Moreover, AP + 2.0% CS was more effective than AP + 1.0% CS to inhibit nucleotide degradation for the same storage conditions. The results were similar to Yang et al (2019), which indicated that CS contained tartary buckwheat extract could effectively delay the ATP decomposition and quality deterioration of tilapia fillets. Zhu, Ma, Yang, Xiao, and Xiong (2016) suggested that the sharp increase of K ‐value lead to the decline of freshness and satisfying flavor, which mainly because of IMP rapidly broke down into HxR and Hx in fish meat.…”
Section: Resultssupporting
confidence: 89%
“…Tartary buckwheat bran (100 g) was extracted with 75% ethanol (1 L) at 70°C for 100 min (DKS28-Water bath kettle; Jinghong Experimental Equipment, Shanghai, Beijing). The obtained mixtures were centrifuged at 6,000×g for 10 min (XHF-D, Xinzhi Biotechnology Co. Ltd.), and then, the precipitates were collected (Yang et al, 2019). Next, the collected precipitate was washed three times, and then, dried at 40°C.…”
Section: Tartary Buckwheat Bran Extract Preparationmentioning
confidence: 99%
“…The difference in fat F I G U R E 3 The color parameters of fresh tilapia fillets with different specifications and partitions. Different capital letters of the same specification indicate significant differences in partitions, and different capital letters in the same partition indicate significant differences in specifications and protein content of fillets will be demonstrated in texture, but as the fish grows, the texture parameters do not show significant differences (Olafsdottir et al, 2004;Yang et al, 2019).…”
Section: Comparison Of the Texture Of Fresh Tilapia Fillets With Different Specifications And Partitionsmentioning
confidence: 99%